Photoacoustics as a tool for the diagnosis of radicular stress: Measurements in eucalyptus seedlings - Barja, P. R.; Mansanares, A. M.; da Silva, E. C.; Alves, PLCA (American Institute of Physics (AIP), 2003)
In reforesting companies (cellulose industry), eucalyptus is usually cultivated in small plastic containers (50 mL). As seedlings remain for about 120 days in these containers-until transplantation-their roots become space restricted, with consequent limitations in water and nutrient absorption. These restrictions may lead to plant stress, decreasing productivity. In this work, we used the photoacoustic technique to evaluate the photosynthetic activity of Eucalyptus grandis, E. urophylla and E. urograndis seedlings subjected to this limited space availability, seeking a correlation with morphological parameters and fluorescence measurements in these seedlings. Photoacoustic, fluorescence, and morphological analysis were conducted every 15 days, from 45 to 120 days after sowing. Fluorescence and photosynthetic rate were evaluated in vivo and in situ, the latter one using the open photoacoustic technique. Data show that root dry matter diminished markedly at 90 and 120 days after sowing; this behavior showed a high correlation with the gas exchange component of the photoacoustic signal, as well as with the fluorescence ratio Fv/Fm. These results indicate that the soil volume of the container becomes insufficient for the roots after 90 days, probably leading to a nutritional deficiency in plants, which explains the decrease observed in the photosynthetic rate of seedlings. (C) 2003 American Institute of Physics.